1972
DOI: 10.1136/adc.47.254.531
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Methods Used in Assessment of Carbohydrate Absorption in Malnourished Children

Abstract: James, W. P. T. (1972). Archives of Disease in Childhood, 47, 531. Comparison of three methods used in assessment of carbohydrate absorption in malnourished children. The results of oral lactose and sucrose tolerance tests were compared with jejunal disaccharidase activities and the absorption rates of lactose and sucrose from a perfused segment of jejunum in 8 malnourished children before and after treatment.Treated children, with nearly normal utilization of circulating glucose, showed a good correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…lactose intolerance, and should be replaced by more mnces in the stool, with reliable methods-such as the H2 test. low pH, if present, are Although we did not aim to use the H2 test for -ntiation (James, 1972; differentiating lactose malabsorption from lactose [ , 1977), but only a few intolerance, we confirmed the observation of Maffei Low these abnormalities. et al (1977) that the increase in H2 excretion tends stools examined showed to be early in lactose-intolerant patients (Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…lactose intolerance, and should be replaced by more mnces in the stool, with reliable methods-such as the H2 test. low pH, if present, are Although we did not aim to use the H2 test for -ntiation (James, 1972; differentiating lactose malabsorption from lactose [ , 1977), but only a few intolerance, we confirmed the observation of Maffei Low these abnormalities. et al (1977) that the increase in H2 excretion tends stools examined showed to be early in lactose-intolerant patients (Fig.…”
Section: Resultssupporting
confidence: 63%
“…Extrapolating therefore not surprising these results to larger populations, the incidence of a ingestion differentiates false normal A-glucose would have been 38-62% Lctose absorption and for lactose malabsorption, and 22-53 % for lactose es, 1972; Harrison and intolerance, and the incidence of a false abnormal intolerance (Garza and A-glucose 9-19 % for lactose tolerance (Table 2). tn and Walker-Smith, Thus, A-glucose during the LTT, appears to bean (James, 1972; Krasilni-unreliable indicator of lactose malabsorption and et al, 1975). lactose intolerance, and should be replaced by more mnces in the stool, with reliable methods-such as the H2 test.…”
Section: Resultsmentioning
confidence: 99%
“… 23 showed that 39% of children with SAM had an abnormal lactose loading test, whereas 16% had an abnormal glucose + galactose loading test before the nutritional recovery. James, 17 however, showed no significant improvement in lactose or sucrose absorption after treatment.…”
Section: Resultsmentioning
confidence: 89%
“… 16 Although not validated, if the blood glucose rises less than 30 mg/100 mL after the oral carbohydrate is administered, then intolerance is considered likely; increments of less than 20 mg/100 mL are generally considered diagnostic of malabsorption. 17 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation